Thinking about laws in political science (and beyond). (30th July 2021) - Weber, Erik; Makhnev, Karina; Leuridan, Bert; Gonzalez Barman, Kristian; De Coninck, Thijs
Abstract: There are several theses in political science that are usually explicitly called 'laws'. Other theses are generally thought of as laws, but often without being explicitly labelled as such. Still other claims are well‐supported and arguably interesting, while no one would be tempted to call them laws. This situation raises philosophical questions: which theses deserve to be called laws and which not? And how should we decide about this? In this paper we develop and motivate a strategy for thinking about laws in political science which integrates two core concepts: spatio‐temporal stability and social mechanisms. The proposed strategy is a set of guidelines that political scientists can use to reflect on and argue about specific cases within their discipline, not a clear‐cut demarcation criterion. We defend and motivate this strategy and apply it to two cases (one with respect to state repression, one about parliamentary elections). After we have developed and motivated our strategy for political science, we show that our proposal is relevant for other disciplines in the social sciences. We explain how our views fit into critical realism and embed them in the debate on laws in general philosophy of science and in the philosophy of the social sciences.